Comparative Study of Δ9-Tetrahydrocannabinol and Cannabidiol on Melanogenesis in Human Epidermal Melanocytes from Different Pigmentation Phototypes: A Pilot Study - Shilpi Goenka (MDPI AG, 2022)
Δ9-tetrahydrocannabinol (THC) is one of the primary ingredients of cannabis plants and is responsible for the psychoactive properties of cannabis. While cannabidiol (CBD), the non-psychoactive compound from cannabis, has been shown to stimulate human epidermal melanogenesis, the effects of THC have not been addressed in human epidermal melanocytes. Moreover, to date, no study has tested the effects of these compounds on melanocytes differing in pigmentation, representative of different skin phototypes, which would be significant as different ethnicities are known to differentially metabolize these xenobiotics. Herein, the effects of THC were studied and compared alongside CBD in human epidermal melanocytes derived from lightly-pigmented (HEMn-LP; Caucasian) and darkly-pigmented (HEMn-DP; African-American) cells over a chronic exposure of 6 d. Results demonstrated that both compounds displayed cytotoxicity at 4 µM but stimulated melanin synthesis and tyrosinase activity in a similar manner in LP and DP cells at nontoxic concentrations of 1-2 µM. However, THC and CBD showed a differential effect on dendricity in both cells; THC and CBD reversibly increased dendricity in LP cells while there was no significant change in DP cells. THC and CBD induced higher levels of reactive oxygen species (ROS) in LP cells while there was no change in the ROS levels in DP cells. In summary, although THC was relatively less cytotoxic as compared to CBD to both LP and DP cells, it exhibited a similar capacity as CBD to stimulate melanin synthesis and export in LP cells which was accompanied by a significant oxidative stress. DP cells were relatively resistant to the effects of both THC and CBD which might implicate the protective effects conferred by melanin in dark-skinned individuals.